Performance Analysis of Stock Mutual Funds and Fixed Income Mutual Funds Before and During the Covid-19 Pandemic - Yunita, Irni; Rinaldi, Muhammad Adrian Daffa Nadino (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the performance of Equity Mutual Funds and Fixed Income Mutual Funds before and during the Covid-19 pandemic, in the period 2018-2020. Using the method of measuring the performance of mutual funds, namely Sharpe, Treynor and Jensen. Then the results of the calculations of the three methods were tested using a non-parametric test, namely the Wilcoxon test using SPPS Software (Statistical Package for the Social Sciences) to find out whether there were differences between stock mutual funds and fixed income mutual funds before and during the covid-19 pandemic. The results obtained from a sample of 54 conventional stock mutual funds and 27 conventional fixed income mutual funds. The results obtained from a sample of 54 conventional stock mutual funds and 27 conventional fixed income mutual funds. Only conventional stock mutual funds with the Jensen method obtained optimal values before and during the Covid-19 pandemic. Then only conventional stock mutual funds with the result value of the Jensen method have different performance from before and during the Covid-19 pandemic. For conventional income mutual funds, there is no difference in performance from before and during the Covid-19 pandemic.